Little monsters : a novel - Brodeur, Adrienne (Avid Reader Press, 2023)
"From the author of the bestselling memoir Wild Game comes a riveting novel about Cape Cod, complicated families, and long-buried secrets-for fans of the New York Times bestsellers The Paper Palace and Ask Again, Yes.Ken and Abby Gardner lost their mother when they were small and they have been haunted by her absence ever since. Their father, Adam, a brilliant oceanographer, raised them mostly on his own in his remote home on Cape Cod, where the attachment between Ken and Abby deepened into something complicated-and as adults their relationship is strained. Now, years later, the siblings' lives are still deeply entwined. Ken is a successful businessman with political ambitions and a picture-perfect family and Abby is a talented visual artist who depends on her brother's goodwill, in part because he owns the studio where she lives and works. As the novel opens, Adam is approaching his seventieth birthday, staring down his mortality and fading relevance. He has always managed his bipolar disorder with medication, but he's determined to make one last scientific breakthrough and so he has secretly stopped taking his pills, which he knows will infuriate his children. Meanwhile, Abby and Ken are both harboring secrets of their own, and there is a new person on the periphery of the family-Steph, who doesn't make her connection known. As Adam grows more attuned to the frequencies of the deep sea and less so to the people around him, Ken and Abby each plan the elaborate gifts they will present to their father on his birthday, jostling for primacy in this small family unit. Set in the fraught summer of 2016, and drawing on the biblical tale of Cain and Abel, Little Monsters is an absorbing, sharply observed family story by a writer who knows Cape Cod inside and out-its Edenic lushness and its snakes"--